Human selective brain cooling during exercise in hot environment - Hirashita, M.; Kajiwara, Y.; Yokokura, S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The study examined the effects of human selective brain cooling during exercise in hot environment.